PENGARUH APLIKASI UREA DAN PUPUK ORGANIK CAIR (URIN SAPI DAN TEH KOMPOS SAMPAH) TERHADAP SERAPAN N SERTA PRODUKSI SAWI PADA ENTISOL - Irna Sofyani Siburian; Retno Suntari; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2016)
Entisols are soils with low organic matter and sandy texture. Soil with this characteristics generally have problems in the provision of nutrients for plants, especially of N due to the high nutrient leaching process. One effort that can be done in addressing the issue is with the addition of inorganic fertilizer and organic fertilizer. Inorganic fertilizers which contain N and frequently encountered is urea. Cow urine and waste compost tea are liquid organic fertilizers which have the potential to be developed as rich elements of N, P, K that are needed by plants. The purposes of this study were to determine the influence of urea and liquid organic fertilizer for crop N uptake and production of mustard (Brassica juncea L), and to determine the optimum dose of urea and liquid organic fertilizer for the production of mustard on Entisols. The results showed that the application of urea and liquid organic fertilizers significantly affected N uptake in mustard. Dose combination of 50% Urea (0.22 g polybag-1) and 50% liquid organic fertilizier (110.91 mL polybag-1) resulted in the highest N uptake value 15.81 g plant-1 compared to the control treatment of 3.11 g plant-1 and resulted in an increase in the height, number of leaves leaf area, fresh weight as well as the mustard dry weight, respectively for 74.88%; 80.00%; 353.95%; 177.40%; 104.73%. Dose combination of 50% Urea (0.22 g polybag-1) and 50% organic liquid fertilizier (110.91 mL polybag-1) was the most effective dose of fertilizier to meet the needs of N in mustard